If it's not what You are looking for type in the equation solver your own equation and let us solve it.
u in (-oo:+oo)
11/8 = u/13 // - u/13
11/8-(u/13) = 0
11/8-1/13*u = 0 // - 11/8
-1/13*u = -11/8 // : -1/13
u = -11/8/(-1/13)
u = 143/8
u = 143/8
| 2.35=t/873.36 | | 7=-3/x+1 | | 2.3=t/873.36 | | y+6/y-4+1=y+1/y-1 | | 3-7b-6y/2b+8b-5y/8b | | 4y-9=3y-6 | | 3y-6=4y-9 | | 2.25=t/873.36 | | 9x+90-(5+2)+5=40 | | 9y+11=10y-18 | | 2y^2+y-16=0 | | x^2+21x-73=0 | | 16=.40x | | 4=36/x-10 | | 8.5x-2=7.5x+6 | | 3x^2+3x-3=y | | 8/9x=-40 | | (11d^8k^3)/6 | | 4(2x-8)-7x=1 | | 28-4x=5x+1 | | 7+4n+6n=13 | | 9z+10=10z-21 | | 10z-21=4z+46 | | 4z+46=10z-21 | | 7z-21=10z-4 | | 10z-4=7z+21 | | 1/3y+5=8 | | 5y=34 | | 35x^2+24x-188=0 | | 35x^2-24x-188=0 | | 4x^2-4x-24= | | 2y+3=y+29 |